2013
DOI: 10.1051/parasite/2013039
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphism of merozoite surface protein-1 and merozoite surface protein-2 inPlasmodium falciparumisolates from children in South of Benin

Abstract: The aim of this study was to determine the genetic diversity of Plasmodium falciparum by analyzing the polymorphism of the msp-1 and msp-2 genes and the multiplicity of infection in children with uncomplicated malaria in southern Benin. Blood samples of children with fever or history of fever with thick smear positive P. falciparum were collected on filter paper. After extraction of DNA by Chelex®, the samples underwent nested PCR. 93 isolates from children were genotyped. For the msp-1 gene, the K1 and R033 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

28
26
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 24 publications
28
26
5
Order By: Relevance
“…This has also consistent with reports from Congo Brazzaville [20], sub-Saharan Africa [13] and Cameroon [22]. but differsfrom genotyping in Benin [23] and Sudan [24]. This suggests that the diversity of P .…”
Section: Discussionsupporting
confidence: 88%
“…This has also consistent with reports from Congo Brazzaville [20], sub-Saharan Africa [13] and Cameroon [22]. but differsfrom genotyping in Benin [23] and Sudan [24]. This suggests that the diversity of P .…”
Section: Discussionsupporting
confidence: 88%
“…is is similar to data reported from other regions of Ghana and countries in sub-Saharan Africa with similar malaria transmission settings [29,[31][32][33]. A study conducted in the south of Benin however reported the FC27 family as the most predominant allelic family [34]. e reported differences in the genetic diversity of P. falciparum infections may be due to host-parasite interactions, transmission intensity, ethnicity, and geographical location.…”
Section: Discussionsupporting
confidence: 87%
“…We found that of the 72 allelic types detected in msp-1, the K1 allelic family with 20.8% allelic frequency besides its representation in poly allelic bands was predominant. This is in line with a previous study from Kolla-Shele area, Arbaminch Zuria District, southwest Ethiopia [46] and studies in Ghana and Benin [51,52]. However, studies in Northern Ethiopia [50] and Malaysia [53] reported Mad20 allele was predominant.…”
Section: Discussionsupporting
confidence: 92%
“…However, the FC27 family was more frequently detected 18(26.1%) in our study. This is consistent with reports from studies in Benin [51] and Sudan [58] but differs from previous study in Ethiopia [57] and Brazzaville, Republic of Congo [47]. This suggests that the diversity of P. falciparum infections may differ according to geographic location, transmission intensity and sample population.…”
Section: Discussionsupporting
confidence: 89%